Physiologically-based pharmacokinetic/pharmacodynamic (PBPK/PD) modeling of 3,3',4,4',5-pentachlorobiphenyl (PCB126) - Lohitnavy, Manupat, author; Yang, Raymond H. S., advisor; Reisfeld, Brad, advisor (Colorado State University. Libraries, 2008)
3,3',4',4',5-Pentachlorobiphenyl (PCB126) is a persistent environment carcinogen. Despite its high lipophilicity, PCB126 was primarily recovered from liver. In addition, PCB126 could achieve its steady state in the liver in a relatively short period of time. Using a three-dimensional quantitative structure-activity relationship (3D-QSAR) model, PCB126 was predicted to be a Mrp2 substrate with a relatively high binding affinity (Km) value. With this newly emerging knowledge, we incorporated a Mrp2-mediated excretion process into our physiologically-based pharmacokinetic (PBPK) model of PCB126. Our model could describe numerous tissue concentration-time courses in different dosing conditions. Our PBPK model revealed an important role of Mrp2 in PCB126 disposition. In addition, to establish a correlation between PCB126 pharmacokinetics and its pharmacodynamic (PD) endpoint (i.e. hepatocarcinogenic effect), we used a chosen internal dose surrogate [i.e. area under the curve of PCB126 in liver (AUCLiver)] to predict the PD effect of PCB126. With this PBPK/PD model, correlation between the AUCLiver and our liver glutathione- S-transferase placental form positive (GSTP+) foci development data was demonstrated. We also conducted a pharmacokinetic interaction study between PCB126 and methotrexate (MTX), a known Mrp2 substrate, by exposing rats with multiple oral doses of PCB126 followed by an oral single dose of MTX. Liver samples were collected and analyzed for hepatic MTX and PCB126 concentration levels. Using a PBPK modeling technique incorporating with competitive inhibition processes between the two chemicals at the level of hepatic Mrp2, liver concentration-time courses of both chemicals were successfully simulated. To further investigate PD effects of PCB126 within liver GSTP + foci, we conducted an experiment by exposing rats with PCB126 using our modified liver foci bioassay up to 6 months. Liver foci positive or negative for GSTP+, transforming growth factor-α+ (TGFα+) and transforming growth factor-β Type 2 receptor (TGFβ2Rc-) were investigated. In rats treated with PCB126, time-dependent changes in all of three biomarkers were observed. Interestingly, when the GSTP+ foci were categorized into four phenotypic groups according to their TGFα and TGFβ2Rc expression, GSTP+ foci with TGFα expression and absence of TGFβ2Rc expression had significantly higher hepatocyte division rates than those of GSTP+ foci without TGFα expression and with TGFβ2Rc expression.
Keywords: GSTP foci; methotrexate; Mrp2; PBPK/PD; PCB126; pentachlorobiphenyl; pharmacokinetics; pharmacology